Descriptive Study on Frequency of Depression in Chronic Hepatitis C (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the frequency of depression in uncomplicated chronic hepatitis C virus (HCV).Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Department of Medicine PMCH Nawabshah from January 2016 to April 2017 using beck depression inventory (BDI).Materials and Methods: 130 patients were selected for this study after taking informed consent to all the patients with chronic hepatitis C were included depression was assessed using BDI.Results: A total 150 pts were enrolled for this study out of them 89 were males and 61 were females with history of HCV more than 6 months depression confirmed by BDI scale.Conclusion: Depression is common in chronic hepatitis C patients, some patients even present with depression, early diagnosis and treatment of chronic hepatitis C and depression patients quality of life is improved and complications can be reduced.